Tanggung Jawab Gubernur Dalam Penanganan Konflik Sosial Pada Negeri Kariuw Dusun Ori Negeri Pelauw Kecamatan Pulau Haruku, Kabupaten Maluku Tengah - Simamora, Raja Arthur; Salmon, Hendrik (Jurnal Saniri, 2024)
Conflict in society certainly conflicts with the identity or identity of the Indonesian nation, namely unity in diversity, and conflict can even result in disruption of national and local stability and obstruction of national and regional development. The government has a responsibility to handle social conflicts so as to create a safe, peaceful, and peaceful community life. The governor's responsibility in handling the conflict between Kariuw State and Pelauw State is not only to prevent re-conflict but also to resolve the conflict at the root of the problem. This paper uses a normative research method, namely research that focuses on providing a systematic explanation that regulates a certain category. The problem approaches used as study material are the statutory approach and the conceptual approach. Collecting legal materials through primary legal materials is then linked to secondary legal materials. The results of the research show that the responsibility of the Governor of Maluku in handling social conflicts that occurred between Kariuw and Pelauw is part of handling social conflicts on a cross-district/city scale, through actions to prevent, stop, and select conflicts, but the Governor of Maluku does not take responsibility into account. This resulted in the Maluku Governor ignoring his legal obligations in handling the conflict. This results in the problem in question not being resolved at the root of the problem. Even though the conditions between Kariuw Country and Ori Hamlet are now calm, there is no conflict. However, a calm situation does not mean that the conflict between the two groups has been resolved to the root of the problem, because handling conflict between the two countries is not only about preventing re-conflict but also resolving the conflict at the root of the problem